Quality Analysis of Health Center Service Management for Efforts to Improve Patient Satisfaction - Jihan Rismawati; Nanda Odelia Gultom (Journal of Economics Business Industry, 2023)
Health Centers providing the best quality of service can affect consumer satisfaction in using services. If the quality of service, facilities, and promotions consumers offer is unsatisfactory, consumers no longer use Health Center services. This research focuses on consumer satisfaction with the services provided by the Health Center after using these services and what attributes need to be improved to increase customer satisfaction. This study aims to determine patient satisfaction with the services provided by Health Center X. The method used in this study is IPA (Importance Performance Analysis). This method, also known as quadrants analysis, aims to measure the relationship between consumer perception and the priority of improving the quality of products or services. Twenty-one attributes or statements represent each service dimension: tangibles, empathy, reliability, responsiveness, and assurance. For the quality of services provided by the Health Center to be improved, the Puskesmas must make improvements as soon as possible to statements that fall into the categories that need improvement, namely the words "Large car or motorcycle parking," "Officers carry out administrative processes quickly and precisely," "The ability of the Health Center to respond to complaints, criticisms, and suggestions from patients," and "Guarantee of trust given by officers to services." Puskesmas gets a customer satisfaction level value of 79.03%, which means that the performance given by the Health Center to customers or patients is included in the Satisfied category.